The Representation of Duplication and Gluing of Almost Symmetric Numerical Semigroup With RF-matrices - Belgin, Ö.; Yılmaz, K.; Hüseyin, T.; Necmettin, K.; Hasan, Ö.; Mehmet, E. (Communications in Mathematics and Applications, 2021)
In this paper, the duplication and gluing of almost numerical semigroup are given by using RF(Row-Factorization) matrices.
Keywords: Almost numerical semigroup; ideals; duplication; gluing; RF-Matrices.